Hepatitis C Virus, Cryoglobulinemia, and Kidney: Novel Evidence - Fabrizio Fabrizi (Scientifica)
Hepatitis C virus infection can lead to chronic active hepatitis, cirrhosis, and liver failure; however, it is also associated with a wide range of extra-hepatic complications. HCV is associated with a large spectrum of histopathological lesions in both native and transplanted kidneys, and it is increasingly recognized as an instigator of B cell lympho-proliferative disorders including mixed cryoglobulinemia. Mixed cyoglobulinemia is a systemic vasculitis primarily mediated by immune complexes; it is characterized by variable organ involvement including skin lesions, chronic hepatitis, glomerulonephritis, peripheral neuropathy, and arthralgias. The most frequent HCV-associated nephropathy is type I membranoproliferative glomerulonephritis, usually in the context of type II mixed cryoglobulinemia. Various approaches have been tried for the treatment of HCV-related glomerulonephritis, including immunosuppressive therapy (corticosteroids and cytotoxic agents), plasma exchange and antiviral agents. Data on the antiviral treatment of HCV-associated glomerulonephritis are not abundant but encouraging results have been provided. Immunosuppressive therapy is particularly recommended for cryoglobulinemic kidney disease. Recent evidence has been accumulated on rituximab therapy for HCV-related cryoglobulinemic glomerulonephritis exists but several questions related to its use remain unclear. Distinct approaches should be considered for the treatment of HCV-associated cryoglobulinemic glomerulonephritis according to the level of proteinuria and kidney failure.